Kinerja return sektor transportasi dan logistik pasca pencabutan PPKM - Saraung, Cris Fritsli (Manajemen Bisnis dan Keuangan Korporat, 2023)
The lifting of restrictions on community activities (or PPKM) in Indonesia on December 30, 2022, has a positive impact on capital market conditions, especially national economic growth. Based on the phenomenon, the purpose of this study is to analyze the growth and performance of the stock return of the transportation and logistics sector after the repeal of PPKM. This study observes from January 1 2023 to April 30 2023 with a sample of listed firms in the transportation and logistics sector. The evidence shows that April has the highest return compared to the previous three months. In addition, this study also finds that April had quite positive stock performance where the risk-return tradeoff became more measurable with a growth of 0.3%. The findings imply that, although not significantly different from previous months, the revocation of PPKM related to national holidays, especially religious holidays, has quite a positive impact on the performance and growth of stock returns in the transportation and logistics sector.